2009
DOI: 10.1007/s12042-009-9037-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Acacia senegal (L) Willd. in Kenya

Abstract: The NERC and CEH trade marks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. 2 The level of genetic diversity and population structure of Acacia senegal variety kerensis 3 in Kenya was examined using seven polymorphic nuclear microsatellite loci and two 4 chloroplast microsatellite loci. In both chloroplast and nuclear datasets, high levels of 5 genetic diversity were found within all pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 63 publications
13
56
4
Order By: Relevance
“…In a previous study, similar results were found with individuals showing mixed ancestry and low differentiation among populations, reflecting strong gene flow of Kenyan populations of Acacia senegal (Omondi et al 2010). Within the genus Inga, Cruz-Neto et al (2014) uncovered a similar pattern in the I. vera species.…”
Section: Genetic Structure and Putative Species Introgressionsupporting
confidence: 68%
See 2 more Smart Citations
“…In a previous study, similar results were found with individuals showing mixed ancestry and low differentiation among populations, reflecting strong gene flow of Kenyan populations of Acacia senegal (Omondi et al 2010). Within the genus Inga, Cruz-Neto et al (2014) uncovered a similar pattern in the I. vera species.…”
Section: Genetic Structure and Putative Species Introgressionsupporting
confidence: 68%
“…The weak population genetic structure together with the lack of isolation-by-distance (data not shown) suggests that species ecology, such as pollen and seed dispersal, and demographic history (impacted by flood) is a strong driver of population structure in the studied I. edulis and I. ingoides populations, as in the case of Acacia senegal (Omondi et al 2010).…”
Section: Genetic Structure and Putative Species Introgressionmentioning
confidence: 90%
See 1 more Smart Citation
“…The species is reproductively active within 2-4 years of establishment. Previous genetic studies of Kenyan populations using both chloroplast and nuclear microsatellites found high genetic diversity within populations and low genetic differentiation among populations, indicating extensive gene flow (Omondi et al, 2010). These attributes demonstrate effective pollen and seed dispersal mechanisms with potential for long-distance dispersal.…”
Section: Introductionmentioning
confidence: 75%
“…Many molecular markers have been used in population and phylogenetic studies in acacias, including inter-simple sequence repeats (ISSRs), simple sequence repeats (SSRs or microsatellites), chloroplastidial DNA and internal and external transcribed spacers (ITS and ETS respectively) (Thompson et al, 2012(Thompson et al, , 2015Omondi et al, 2010Omondi et al, , 2016Harris et al, 2012;Miller et al, 2011;Le Roux et al, 2011Fredua-Agyeman et al, 2008;Mulumba et al, 2012;Josiah et al, 2008;Ndlovu et al, 2013;Murphy et al, 2010;Brown et al, , 2012. Furthermore, several SSRs markers have been developed for Acacia species, such as A. atkinsiana (Levy et al, 2014), A. brevispica (Otero-Arnaiz, 2005.…”
Section: Introductionmentioning
confidence: 99%